Hubungan Riwayat Makanan Pendamping ASI dan Perilaku Makan Orang Tua dengan Status Gizi Anak Picky Eater : Correlation between History of Complementary Breastfeeding Food and Eating Behavior of Parents with Nutritional Status of Picky Eater Children - Rasunah Mutiara Shintya; Hari Ghanesia Istiani; Eka Rokhmiati (MPI Press, 2023)
Introduction: Picky eater is a picky eating behavior in children. Picky eaters are a common problem with children's eating patterns. The factors that cause picky eaters are a history of complementary foods and parental eating behavior. A good child's diet will affect the nutritional status of children to be good. Objective: To determine the relationship between the history of complementary feeding and the eating behavior of parents with the nutritional status of picky eater children. Methods: This research design uses correlation with a cross-sectional approach. A sample of 52 respondents was taken using purposive sampling. Data were collected by questionnaire and analyzed using Chi-square. Result: Statistical test using Chi-Square test with a significance level of a = 0.05 or 95%. The results of the research found that the value of p = 0.012 < a = 0.05 and p = 0.043 < a = 0.05. Conclusion: There is a significant relationship between the history of complementary feeding and parents’ eating behavior with the nutritional status of picky eater children.